BRIDGING TRADITION AND TECHNOLOGY: THE ROLE OF E-COMMERCE AND SOCIAL MEDIA IN JAIPUR’S HANDICRAFT MARKETING - Mathur, Megha; Ranawat, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the integration of e-commerce and social media in the marketing of Jaipur’s traditional handicrafts. The study investigates how these modern technological tools are being utilized to promote and sell handcrafted products, bridging the gap between centuries-old artisanal traditions and contemporary digital platforms. Through a mixed-methods approach, including surveys, interviews, and case studies, the research examines the impact of e-commerce and social media on sales, brand awareness, and the preservation of Jaipur’s handicraft heritage. The findings reveal significant opportunities for artisans and businesses to expand their reach and enhance their marketing strategies, while also highlighting challenges in adopting and effectively utilizing these digital tools.